Examining the relationship between symptoms watched in lung cancer patients and illness perception - Ozlem Ugur; Ezgi Karadag; Hatice Mert; Cansu Kosar Sahin; Tugba Yardimci; Haydar Soydaner Karakus (Journal of the Pakistan Medical Association, 2022)
Objective: To examine the relationship between the symptom experience of lung cancer patients and their illness perception of the disease. Methods: The descriptive and cross-sectional study was conducted from April to September 2015 at the Chemotherapy Treatment Centre of the Medicine Chest Diseases Clinic at the Ege University, Izmir, Turkey, and comprised lung cancer patients of either gender aged >18 years. Data was collected using a predesigned Patient Questionnaire as well as the standard Lung Cancer Symptom Scale, Illness Perception Questionnaire and Karnofsky Performance Scale. The patients' sociodemographic characteristics and data on their illness, the symptoms they experienced and the numerical and percentage distribution of the items on the illness perception scale, mean and standard deviation values were examined. Pearson Correlation analysis was used to examine the correlation between illness perception and Karnofsky Performance Scale scores and other variables. Results: Of the 105 patients, 86(81.9%) were males, 86(81.9%) were married, 49(46.7%) were elementary school graduates, 101(96.2%) were unemployed, and 95(90.5%) were receiving chemotherapy. The overall mean age of the sample was 61.43±8.24 years, the period since diagnosis was 11.38±17.84 months, and the duration of chemotherapy was 4.28±2.37 months. The mean symptom burden score was 22.75±10.85 and the Lung Cancer Symptom Scale score was 22.75±10.85). The mean score of the type of illness domain was was 5.53±2.12. The overall mean global quality of life score was 64.30±12.60. ---Continue